2017
DOI: 10.1016/j.apsusc.2017.01.211
|View full text |Cite
|
Sign up to set email alerts
|

Laser polishing of 3D printed mesoscale components

Abstract: Process optimisation for laser polishing novel 3D printed SS316L parts  Evaluating the effects of key polishing parameters on SS316L surface roughness  Detailed spectroscopic analysis of oxide layer formation due to laser polishing  Comparative surface integrity analysis of SS parts polished in air and argon  A maximum reduction in roughness of over 94% achieved at optimised polishing settings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(93 citation statements)
references
References 44 publications
3
85
0
5
Order By: Relevance
“…The lower strength of unpolished Cu/PLA sample is primarily due to the gaps and the extensive porosities inside the sample because of the poor printing quality. After laser polishing, the porosity and bulk defects are reduced, and the interface bonding between the Cu fiber and the PLA matrix is improved, resulting in an increase in polymer chain anchoring on the fiber . From Table , it is observed that after laser polishing, the elongation‐at‐break decreases by 24.41%, 32.83%, 28.37%, and 37.84% for S1, S2, S3, and S4, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower strength of unpolished Cu/PLA sample is primarily due to the gaps and the extensive porosities inside the sample because of the poor printing quality. After laser polishing, the porosity and bulk defects are reduced, and the interface bonding between the Cu fiber and the PLA matrix is improved, resulting in an increase in polymer chain anchoring on the fiber . From Table , it is observed that after laser polishing, the elongation‐at‐break decreases by 24.41%, 32.83%, 28.37%, and 37.84% for S1, S2, S3, and S4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Laser polishing is performed by irradiating a laser beam with a certain energy density and wavelength on a material to melt or evaporate the surface layer of the material to obtain a smooth surface. This method does not require any mechanical abrasives or polishing tools and can polish surfaces with very complex topography that are difficult or impossible to polish with conventional polishing methods . Laser polishing has so far been used to polish a variety of materials, including diamonds, glass, ceramics, and various metals .…”
Section: Introductionmentioning
confidence: 99%
“…Macrostructure smoothing can be achieved by applying continuous wave (cw) laser radiation, this process is known as laser polishing (LP) and it is mainly focused on improving the surface quality of AM components via demolishing surface asperities. Although several attempts have been made to examine the effects of laser polishing and the resulting surface roughness, there has been no detailed and thorough investigation of the effect of process parameters on the generated surface, to enable prediction and optimisation of the process responses [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the total porosity, pore size and size distribution cannot be controlled (Kasperovich et al, 2016). Therefore, post-processes such as mechanical polishing, chemical etching, heat treatment and anodizing are very crucial (Tarafder et al, 2013;Sadie and Subramanian, 2014;Pequegnat et al, 2015;Bhaduri et al, 2017;Shamvedi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%